Hypericin Exerts Detrimental Effect on Huh-7 As a Delegacy of Hepatocellular Carcinoma: A P53 Dependent Pathway: - Zaferani Arani, Hamid; Olya, Maedeh; Shekarriz, Amirhossein; Zabolian, Amirhossein; Zare Marzouni, Hadi; Aryan, Hoda; Hoseinian, Mohammad; Javidi, Mohammad Amin; Atashi, Hesam Adin (Galen Medical Journal, 2020)
Background: Hepatocellular carcinoma is the most common type of liver cancer which arises from the main cells in the liver. We address many studies investigating anti-cancer role of hypericin, however the proposing corresponding molecular pathway seems to be still a debate. Therefore, the present study aimed to evaluate the apoptotic effect of hypericin on the Huh7 as the liver cancer cell line and its relation with the gate keeper gene P53. Materials and Methods: In this study, the Huh7 cell line and fibroblast cells (as control group) were treated with different concentrations of hypericin for 24 and 48 hours. Detection of cell death was performed by MTT assay and flow cytometry. The expression of bax, bcl2 and p53 mRNAs was evaluated by Real-time PCR. Also, Immunocytochemistry (ICC) analysis was used for further evaluation of P53expression. Results: The results showed that hypericin has a dose-dependent cytotoxic effect on the Huh7 cell line, with no or marginal effect on fibroblastic cells. According to flow cytometry results, about 53%cells underwent apoptosis after exposure to LD50 of hypericin for 24 hours. Real-time PCR data demonstrated that the pro-apoptotic genes Bax and P53 expression level increased. Expectedly ICC results confirmed the up-regulation of P53 proteins in treated samples. Conclusion: Our results indicate the cytotoxicity of hypericin on Huh7 cells by affecting the expression of the gate keeper gene P53; furthermore it is suggested that this herb can be utilized simultaneously with modalities targeting P53 up-regulation or related molecular pathways. [GMJ.2020;9:e1896]